Public debt in the state finance (2014)
This paper describes the Colombian public debt situation between 2000 and 2012. First, it shows the history, the current structure, classification and major differences of this. Next, the balance’s results of both internal and external public debt, separated by National Government and a Territorial Level and describing its composition and evolution. Then it specify some causes of improved indicators, how much it was due to changes in debt structure, and an analysis of debt service, its components and how was it behavior respect to the Gross Domestic Product. Finally, it have a presentation about the sustainability of the debt.